Ultrafiltration combined with size exclusion chromatography efficiently isolates extracellular vesicles from cell culture media for compositional and functional studies. Issue 1 (December 2017) - Benedikter, Birke; Bouwman, Freek; Vajen, Tanja; Heinzmann, Alexandra; Grauls, Gert; Mariman, Edwin; Wouters, Emiel; Savelkoul, Paul; Lopez-Iglesias, Carmen; Koenen, Rory; Rohde, Gernot; Stassen, Frank
Abstract Appropriate isolation methods are essential for unravelling the relative contribution of extracellular vesicles (EVs) and the EV-free secretome to homeostasis and disease. We hypothesized that ultrafiltration followed by size exclusion chromatography (UF-SEC) provides well-matched concentrates of EVs and free secreted molecules for proteomic and functional studies. Conditioned media of BEAS-2B bronchial epithelial cells were concentrated on 10 kDa centrifuge filters, followed by separation of EVs and free protein using sepharose CL-4B SEC. Alternatively, EVs were isolated by ultracentrifugation. EV recovery was estimated by bead-coupled flow cytometry and tuneable resistive pulse sensing. The proteomic composition of EV isolates and SEC protein fractions was characterized by nano LC-MS/MS. UF-SEC EVs tended to have a higher yield and EV-to-protein rate of purity than ultracentrifugation EVs. UF-SEC EVs and ultracentrifugation EVs showed similar fold-enrichments for biological pathways that were distinct from those of UF-SEC protein. Treatment of BEAS-2B cells with UF-SEC protein, but not with either type of EV isolate increased the IL-8 concentration in the media whereas EVs, but not protein induced monocyte adhesion to endothelial cells. Thus, UF-SEC is a useful alternative for ultracentrifugation and allows comparing the proteomic composition and functional effects of EVs and free secreted molecules.